Mastering Autodesk Revit 2018 - Kim, Marcus; Krygiel, Eddy, 1972-; Kirby, Lance (Sybex, a Wiley brand, 2017)
Provides guidance for all skill levels to learn how to perform tasks using Autodesk Revit for Architecture.